2 - Funding Higher Education in Africa: State, Trends and Perspectives - Damtew Teferra, (Journal of Higher Education in Africa, 2013)
This article discusses and analyzes the state of funding higher education in Sub-Saharan Africa (SSA). The article, based on nine case study countries, examines the cost of higher education, current and potential funding sources and policy discourses that shaped funding trends in the region. The study further explores policies, trends and factors that hindered, as well as promoted, funding the sector in SSA and the role of external players in doing so. It also articulates poorly tapped and potential sources of funding for the higher education system. It concludes by providing some policy recommendations, taking into account the mounting challenges of expansion which are pushing the cost of higher education to unsustainable levels.